PENGARUH KESADARAN WAJIB PAJAK, TINGKAT PENGHASILAN DAN AKUNTABILITAS PELAYANAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus Pada Kantor Samsat Surakarta) - Widi, Giovani; Suharno, Suharno; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Taxpayer compliance is that taxpayers must fulfill their obligations to paytaxes in accordance with taxation laws and regulations. The purpose of this studywas to determine (1) The effect of taxpayer awareness on motor vehicle taxpayercompliance (2) The effect of income levels on motor vehicle taxpayer compliance(3) The effect of public service accountability on motor vehicle taxpayercompliance. This study uses primary data in the form of a questionnaire. Thepopulation in this study is the number of motor vehicle taxpayers at the SurakartaSamsat Office. The sampling technique in this study used a randomi ed method.This study uses multiple linear regression analysis techniques with the resultsshowing that taxpayer awareness has a significant effect on motor vehicletaxpayer compliance, income levels do not have a significant effect on motorvehicle taxpayer compliance, and public service accountability has no significanteffect on motor vehicle taxpayer compliance. .